PENERAPAN METODE IMLA’ AL-IKHTIBARI DALAM MENINGKATKAN KOMPETENSI MENULIS BAHASA ARAB PADA SISWA KELAS X DAYAH ERPADU AL-MUSLIMUN - Azizah, Azizah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
The researcher chose this title because it was motivated by students who were lazy in writing Arabic in the Imla' lesson. This paper is entitled "Application of the Imla 'Al-Ikhtibari Method in Improving Arabic Writing Competence in Class X Students of Integrated Dayah Almuslimun". The purpose of this study was to find out how the application of the method applied in writing competence in Arabic for Class X Integrated Dayah Almuslimun students. The research method used by the researcher is quantitative research with experimental type, and uses pretest and posttest. The population in this study were all students of class X Integrated Dayah Almuslimun, the sampling technique used was non-probability sampling with total sampling technique. The sampling technique used in this study is total sampling. The test results show that the pretest and posttest data collection function is to determine the students' initial and final abilities towards the material associated with their learning outcomes. The average value for the pretest = 60.13 while the posttest is 84.74 the standard deviation of the pretest is 6.827 while the post-test is 7.066. So it can be concluded that this study is in a good category by looking at the difference in results from before and after treatment. Thus, the application of the imla' al-ikhtibari method in improving Arabic writing competence in class X Dayah Terpadu Almuslimun students helps students improve their writing skills in Arabic.